IMPACT OF ENERGY PRICES ON PRICES OF BASIC TOURISM SERVICES IN THE EURO AREA - Lachezar Borisov (Baltic Journal of Economic Studies)
The tourism sector in the euro area has faced several challenges over the last five years. After a period of accelerated development, tourism is facing a serious challenge caused by the COVID-19 crisis and a decline in the number of tourists and in tourism services provided. The period of recovery has been accompanied by significant inflationary processes and a shock increase in the prices of energy products, further provoked by the war on the territory of Ukraine. Furthermore, there has been a notable surge in the cost of services within the tourism industry. In light of these developments, it is imperative to investigate the interconnections between energy prices and those in the hotel and restaurant sector. The primary objective of this study is to ascertain the causal relationship between energy inflation and inflation in the hotel and restaurant sector across various periods of crises and external influences on the sector. This analysis seeks to elucidate the causal relationship between energy inflation and inflation in the hotel and restaurant sector. It is based on official statistics published by Eurostat for the euro area, utilising monthly data from the Harmonised Index of Consumer Prices, with a particular focus on the groups "Electricity, gas and other fuels" and "Restaurants and hotels". The results of the testing indicated that the highest correlation between the series of the annual inflation rate of energy products and the inflation rate of services provided by hotels and restaurants was observed when different lags were employed. Following the identification of the highest values of Pearson's coefficient between the inflation rate of energy products and the annual increase in the prices of services provided by hotels and restaurants, a dynamic analysis was conducted. The primary focus of the study is a regression analysis conducted with a predetermined monthly lag. The regression analysis revealed a causal relationship between the prices of hotels and restaurants and the dynamics of energy product prices, thereby enabling the prediction of the former based on the latter. The study reveals the existence of a specific functional relationship. The null hypothesis, which states that there is no causal link between energy product prices and the prices of services provided by hotels and restaurants, is also rejected. The statistical significance of the causal relationship between the two indices is demonstrated. A correlation analysis reveals a relationship between the monthly inflation rates for the categories "Electricity, gas and other fuels" and "Restaurants and hotels" on an annual basis. Furthermore, the two indices exhibit comparable dynamics with a lag of seven months. In particular, the price dynamics of energy products can be employed to forecast the price dynamics of the hotel and restaurant sector after a seven-month period. Moreover, the regression analysis indicates the existence of a statistically significant functional, linear relationship between inflation in energy products and inflation in basic tourism services. It seems plausible to suggest that the fluctuations in energy prices observed during the period 2019-2024 could serve as an indicator of potential shifts in the pricing of basic tourism services. In light of these findings, it is possible for euro area governments to implement targeted measures, while tourism managers can devise bespoke strategies.